The role of breaking synoptic scale Rossby waves for the North Atlantic oscillation and its coupling with the stratosphere - Kunz, Torben (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2008)
This thesis investigates, from a modeling and observational perspective, the role of breaking synoptic scale Rossby waves for the North Atlantic oscillation (NAO) and its coupling with the stratosphere. The issue is addressed from three different approaches: (i) Forced-dissipative simulations with a simplified general circulation model are carried out to investigate both, the evolution of baroclinic wave packets in a mid-latitude eddy-driven jet which result in either anticyclonic (AB) or cyclonic wave breaking (CB) during their saturation stage, and its sensitivity to stratospheric flow conditions. (ii) Adiabatic and frictionless simulations of individual baroclinic wave life cycles are performed, using different initial stratospheric flow conditions to study its influence on baroclinic wave breaking. (iii) Observational data are used to analyze AB and CB events in the North Atlantic sector. Their impact on the NAO and its connection to the stratosphere is investigated by a composite analysis, based either on wave breaking events in the troposphere or on episodes of negative stratospheric northern annular mode (NAM). From the synthesis of the results of these approaches, the following picture is obtained: (1) Stratospheric perturbations (characterized by a negative NAM) appear first in at upper stratospheric levels and propagate downward into the lower stratosphere where they persist for about two months. (2) As a response, the behavior of tropospheric baroclinic waves is changed through a non-linear wave-mean flow interaction, with the consequence of more frequent CB than AB events. (3) This change in wave breaking frequencies is intimately linked --- by a positive feedback --- with a concurrent negative NAO anomaly at the Earth's surface. (4) Baroclinic wave packets of AB- (CB-) like behavior drive meridional circulation dipoles resembling the positive (negative) phase of the NAO. (5) A distinct asymmetry is found between the two kinds of synoptic scale wave breaking: Major AB events emerge from eastward and ...